Problematika Pembelajaran Bahasa Indonesia Di Sekolah: Faktor Guru, Siswa, Serta Media Pembelajaran - Hendarti Hendarti (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The issues in school learning are diverse, with several factors contributing to these challenges, including teachers, students, and the learning media used by teachers. Every teacher must continuously innovate in creating learning media that meet the needs of students. This can help minimize the challenges in teaching the Indonesian language in the classroom. Meanwhile, student learning factors and media also impact the Indonesian language learning process. Students often face difficulties in understanding the language or information being taught, which lowers their interest in learning. Additionally, the media used are often less effective and lack interactivity, failing to meet the current needs of students. This includes limited use of technology or a wide range of digital learning resources, indicating that the combination of student limitations and poor adaptation represents a significant challenge for effective and engaging Indonesian language learning.